Efektivitas Media Audiovisual Berbantuan Canva dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar pada materi Iklim dan Perubahannya - Siti Rohmatul Jannah; Hartono; Farhan Yadi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and examine the effectiveness of a Canva-assisted audiovisual learning medium on the topic of Climate and Its Changes in elementary schools. The research employed a research and development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 30 fourth-grade students from SD Negeri Rantau Pangeran and SD Negeri Talang Nyamuk. The resulting product was an interactive video that combines text, animation, images, and audio to visualize abstract climate concepts. Expert validation results indicated a very high level of validity with an average score of 92.80%, covering aspects of media, material, and language. The practicality test obtained scores ranging from 76% to 100%, categorized as practical to very practical. The effectiveness test showed a significant improvement in students’ learning outcomes, as evidenced by an increase in the average pretest score from 54.67 to 82.33 in the posttest, with an N-Gain value of 0.63 (moderate category). These findings demonstrate that the Canva-assisted audiovisual medium is feasible to be used as an alternative for science learning, as it can enhance conceptual understanding, scientific skills, science literacy, and learning motivation among elementary school students.